Clinical outcomes of patients infected with HIV through use of injected drugs compared to patients infected through sexual transmission: late presentation, delayed anti‐retroviral treatment and higher mortality. (14th April 2016) - Suárez‐García, Inés; Sobrino‐Vegas, Paz; Dalmau, David; Rubio, Rafael; Iribarren, José Antonio; Blanco, José Ramón; Gutierrez, Félix; Montero Alonso, Marta; Bernal, Enrique; Vinuesa García, David; del Amo, Julia; ,
Abstract: Aims: To compare patients who acquired HIV infection through use of injected drugs (HIV‐IDU) with patients who acquired HIV by sexual transmission (HIV‐ST) in terms of late presentation (LP), delay in anti‐retroviral treatment (ART) initiation, virological and immunological response to ART, mortality and progression to AIDS. Design: Prospective multi‐centre cohort study of HIV‐infected subjects naive to ART at entry (Cohort of the Spanish HIV Research Network: CoRIS). Setting: Thirty‐one centres from the Spanish public health‐care system. Participants: A total of 9355 patients were included (1064 HIV‐IDU and 8291 HIV‐ST) during 2004–13. Measurements: We compared LP (defined as presentation for care with a CD4 cell count < 350/μl and/or AIDS‐defining illness), delayed ART initiation (defined as initiating treatment more than 6 months after the date when treatment was indicated by the guidelines, or not initiating treatment at all when it was indicated), virological and immunological response to ART (defined as viral load < 50 HIV‐1 RNA copies/ml and a CD4 count increase of at least 100 cells/μl, respectively, after 1 year of treatment), mortality and progression to AIDS in HIV‐IDU and HIV‐ST. Findings: Compared with HIV‐ST, HIV‐IDU had higher risk of LP [odds ratio (OR) = 1.76; 95% confidence interval (CI) = 1.41–2.18], delayed ART initiation (OR 1.87; 95% CI = 1.46–2.40) and higher mortality [hazard ratio (HR) = 1.43; 95% CI = 1.03–2.01] and risk of progression to AIDS [subhazard ratio (SHR) = 1.68; 95% CI = 1.29–2.18]. Virological suppression due to ART was lower in HIV‐IDU than in patients with HIV‐ST only among patients without hepatitis C virus (HCV) infection [adjusted OR (aOR) = 0.59; 95% CI = 0.36–0.95]; among patients with HCV infection, virological suppression due to ART did not show significant differences between HIV‐IDU and HIV‐ST. There were no significant differences in immunological response after adjusting by HCV (aOR = 0.74; 95% CI = 0.52–1.06). Conclusions: In Spain, patients who acquire HIV infection through use of injected drugs appear to have a higher risk of late presentation, delayed initiation of anti‐retroviral treatment and progression to AIDS and death than patients who acquire HIV by sexual transmission.